English: English - Ekawati Ekawati; Nasarudin Umar; Jerry Hendrajaya; Fatkhul Mubin (Balai Penelitian dan Pengembangan Agama Jakarta, 2022)
This study aims to: 1) determine the influence of tarekat on radicalism and religious fundamentalism movements. 2) describe the role of tarekat in building multicultural society harmonization. 3) knowing the impact of tarekat in preventing radicalism and religious fundamentalism in a multireligious society.The method usedis qualitative research methods and the hypothesis in this research showing there is an influence of tarekat teachings on radicalism and religious fundamentalism: the higher the spiritual value of a person through the tarekat, the more respects the rights of others, He does not harm and threatens the lives of others and able to create a safe and comfortable atmosphere in the life of the nation and state.Tarekat also implements on socio-psychological changes and behaviors related to social communities. These changes are related to the understanding of the values of tawhid which are integrated in each teaching which plays a very important role in building a multicultural harmonization of society.